Love of Marko Kraljević in epic folk poems from Kosovo and Metohija (motive for conflict and resolving key) - Miljković, Marija D. (Collection of Papers of the Faculty of Philosophy in Priština, 2015)
Love of Marko Kraljević in heroic poems from Kosovo and Metohija has а significant place. Whether she is directly involved or her role is veiled, it is evident that without her epic biography of hero would not be complete. Faithfull love proves loyalty in crucial moments and with that justifies trust of her master. Often, she is direct motive for conflict and in the specific situation she is described like indirect problem initiator as well as the key for its resolving.